The Role of Congestion Index as Predictor Short-term Clinical Outcome in Patients AHF - Veny Kurniawati; Anna Fuji Rahimah; Cholid Tri Tjahjono; Mohammad Saifur Rohman; Yoga Waranugraha (Heart Science Journal, 2020)
IntroductionCongestion is the major problem in Acute Heart Failure (AHF) patients. Despite improving clinical congestion, we should assess and treat the hemodynamic congestion to decrease the progression of the disease and improve outcome of AHF patients. This study assess the ability of congestion index, a simple echocardiography parameter using ePCWP + eRAP to predict short-term clinical outcomes of AHF patients compare with NT-proBNP.Methods This prospective cohort study was conducted at Saiful Anwar General Hospital Malang from January 2108 to July 2019. AHF patients treated according to the 2016 ESC guidelines for AHF. Hemodynamic congestion was defined if congestion index (ePCWP+eRAP) at hospital discharge ≥ 30 mmHg.NT-proBNP level, ePCWP and eRAP were measured at 0-12 hours hospital admisssion and at hospital discharge. Clinical follow-up over a period of 30 days, AHF rehospitalization and mortality due to cardiovascular was registered. ResultsThis was a prospective study of 62 patients hospitalized with AHF. All patients were NYHA functional class IV. AHF mortality and rehospitalization rates in this study were 12.9% and 20.9%, respectively. Patient with congestion index ≥30 mmHg showed a higher 30 day rehospitalization [10 [66.7%] vs 3 [6.4%]; P =0.000; CI 95% OR 7.53(3.11-18.2)] and cardiovascular mortality [7 [46.7%] vs 1 [2.1%] P=0,000; CI 95% OR 5.90(2.95-11.78)]. NT-proBNP level at hospital discharge (cut off 5853 pg/mL; sensitivity 92%; specificity 91%; AUC 0.945; P = 0.000) was better than congestion index (cut off 30 mmHg; sensitivity 92.9%; specificity 91.7%; AUC 0.914; P = 0.000) in predicting AHF rehospitalization. For predicting mortality, NT-proBNP level at hospital discharge (cut off 8733 pg/mL; sensitivity 87.5%; specificity 88.9%; AUC 0.940; P = 0.000) were better than congestion index (cut off 31 mmHg; sensitivity 87.5%; specificity 81.5%; AUC 0.890; P = 0.000). ConclusionCongestion index could predict AHF rehospitalization and mortality within 30 days in patients with AHF.